The A(ffect) B(ehavior) C(ognition) D(ecision) of parasocial relationships: A pilot study on the psychometric properties of the Multidimensional Measure of Parasocial Relationships (MMPR). Issue 10 (October 2022) - Garcia, Danilo; Björk, Elina; Kazemitabar, Maryam
Abstract: The aim of this pilot study was to preliminary test the psychometric properties of the Multidimensional Measure of Parasocial Relationships (MMPR), a self-report that assess people's attitude ( affect, cognition, and behavior ) towards social media figures and to what extent people perceive that media figures influence their daily life decisions (e.g., consumption, exercise, nutrition). In short, the MMPR measures how and to what extent people are committed to such one-sided relationships and interactions through social media platforms. Besides factor structural analyses (four different models) and internal consistency, we also tested the MMPR's concurrent validity by investigating if, as hypothesized, the association between commitment to parasocial relationships and self-esteem is mediated by its positive association to social comparison. Participants ( N = 259) answered to the MMPR, the Iowa-Netherlands Comparison Orientation Measure, and the Rosenberg Self-Esteem Scale. As expected, the MMPR loaded in four dimensions and had good internal consistency (e.g., Cronbach's Alphas were between .66-.75 for the four dimensions and .85 for the whole measure). The bifactor model with correlated factors had the best fit indexes ( CFI = .95, RMSEA = .07). Moreover, the direct effect of MMPR was positive on social comparison ( β = .18, p < .01), the direct effect of social comparison on self-esteem was negative ( β = -.51, p < .001), and the indirect effect of MMPR on self-esteem was negative ( β = -.09, p < .01). In sum, our results suggest that parasocial relationships through social media platforms consist of four necessary and correlated dimensions (A: Affective; B: Behavioral; C: Cognitive; and D: Decisional). Moreover, the MMPR successfully assessed that high level of commitment with parasocial relationships are positively associated with the tendency to compare oneself to others, which in turn leads to low levels of self-esteem. Hence, the MMPR has sound psychometric properties and is a good candidate for further analyses. Abstract : Classical Test Theory; Parasocial Interactions; Parasocial Relationships; Self-Esteem; Social Comparison Orientation; Social Media.